Monostotic Paget’s disease of bone – literature review and case report - Piotr Wysiński; Magdalena Krajewska-Włodarczyk (Rheumatology, 2019)
Paget’s disease of bone (PDB) is a localized, chronic bone metabolic disorder, characterized by an osteoclastic malfunction, causing increased bone resorption and subsequent compensatory creation of new bone with a defective microstructure. Monostotic cases of PDB are less common than asymmetrical polyostotic PDB cases. The radiological diagnosis of PDB is usually straightforward, but monostotic cases can cause diagnostic difficulties. We report a case of monostotic PDB in a 64-year-old man. He experienced pain of the left lower extremity and radiological investigations revealed irregular areas of bone destruction in the left femur. Bone biopsy findings indicated PDB. Treatment with bisphosphonates was initiated, but after about three years of treatment left hip arthroplasty was required due to a large area of bone destruction. Presentation of this case report aims to discuss diagnostic challenges of monostotic cases of PDB and present guidelines of treatment.